Quadriceps Strain and TKA: Contribution of the Tourniquet and Intramedullary Rod to Postoperative Thigh Pain: A Randomized Controlled Trial. (15th March 2023) - Stocks, Gregory W.; Odoemene, Melissa; Gex, Julia; Vidal, Emily A.; Sawyer, Kathryn; Jones, Stephen L.; Thompson, Brandon; Laughlin, Mitzi S.
Abstract : Background: Thigh pain is relatively common after total knee arthroplasty (TKA) and has been attributed to compression of the thigh muscles by the tourniquet used during surgery. Thigh pain that occurs after a TKA that was performed without a tourniquet may be due to a strain of the quadriceps muscle or insertion of the intramedullary (IM) rod. The purpose of the present study was to determine the cause of thigh pain after TKA in a randomized controlled trial evaluating tourniquet use, IM rod use, and quadriceps strain. Methods: This prospective randomized controlled trial enrolled 97 subjects undergoing primary knee arthroplasty into 4 groups according to tourniquet use (yes or no) and IM rod use (yes or no). Quadriceps strain was evaluated with magnetic resonance imaging (MRI) on postoperative day 1 (POD 1). Data collected preoperatively, intraoperatively, and postoperatively until the 6-week clinical visit included pain levels for the knee and thigh (recorded separately) and knee range of motion. Results: Regardless of tourniquet or IM rod use, 73 (75%) of the 97 patients reported thigh pain on POD 1. Thigh pain at 2 weeks postoperatively was indicative of a quadriceps strain. Use of a tourniquet and patient-reported thigh pain at 2 weeks increased the odds of a quadriceps strain, whereas IM rod use did not significantly contribute to thigh pain. Conclusions: The etiology of thigh pain after TKA may be multifactorial; however, an iatrogenic quadriceps strain is one source of thigh pain after TKA, especially if the pain persists 2 weeks after surgery. Level of Evidence: Prognostic Level I . See Instructions for Authors for a complete description of levels of evidence.